2005
DOI: 10.1007/s10549-004-3003-3
|View full text |Cite
|
Sign up to set email alerts
|

Papillary lesions of the breast: a molecular progression?

Abstract: Our data suggest an involvement of chromosome 16 mutations in the early steps of breast papillary tumorigenesis. TP53 deletion and possibly LOH at 16q23 appear to play a role as progression factors, being they significantly associated with malignant transformation of breast papilloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Although intra-tumoral heterogeneity may result in discordant cytogenetic profiles, this minor effect may be considered negligible when distinguishing malignant from benign samples by our 14 method. Moreover, cytogenetic profiles of five cancer cases showed 16q loss and 1q gain as the most frequently altered region, which is a typical cytogenetic profile of papillary breast carcinomas, as reported previously [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although intra-tumoral heterogeneity may result in discordant cytogenetic profiles, this minor effect may be considered negligible when distinguishing malignant from benign samples by our 14 method. Moreover, cytogenetic profiles of five cancer cases showed 16q loss and 1q gain as the most frequently altered region, which is a typical cytogenetic profile of papillary breast carcinomas, as reported previously [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 80%
“…There are many reports indicating the presence of genomic alterations in intracystic papillary carcinoma of the breast [16][17][18][19][20]. We recently reported that genome-wide copy number aberrations could easily be detected by array comparative genomic hybridization (aCGH), which could then be used to quantify GIN, and that intracystic papillary carcinoma harbors significant GIN compared with intracystic papilloma [21].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 104 cases, 30 were mammotome core needle biopsies, all done for calcifications (14-gauge) and 74 were ultrasound-guided (16-, 18-, or 20-gauge). The average number of ultrasound-guided core cylinders obtained per patient was 5 (range, [3][4][5][6][7][8][9][10][11][12]; for mammotome core needle biopsy it was 15 (range, [10][11][12][13][14][15][16][17][18][19][20]. The diagnoses on the excision specimens were as follows: no residual intraductal papillomas, 16 (15.3%); residual intraductal papillomas, 71 (68.3%); atypical duct hyperplasia, 8 (7.7%); ductal carcinoma in situ, 6 (5.8%); and invasive carcinoma, 3 (2.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Several subsequent studies looking at large-scale chromosomal alterations (using methods of fluorescence in situ hybridization, loss of heterozygosity, and comparative genomic hybridization) have generated conflicting data regarding the presence or frequency of alterations in benign papillary lesions. [4][5][6][7][8][9] Thus, it is unclear whether papillary neoplasms harbor genetic changes common to the pathways of breast cancer progression, and it remains undetermined whether papillary lesions represent precursors of breast carcinoma.…”
mentioning
confidence: 99%